Narrativised Historicity in Arif Anwar’s The Storm - Nishat Atiya Shoilee (Asiatic: IIUM Journal of English Language and Literature, 2023)
With five different plotlines over a prolonged course of sixty years in British Bengal and East Pakistan, Canadian-Bangladeshi writer Arif Anwar’s debut novel The Storm (2018) captures historical ethos through a series of micronarratives. An occupied Burma during WWII, a 1965 pre-Partition Calcutta, and a devastated Bhola after the 1970 cyclone — all these feature in this historiographic metafiction. Each character contributes as an independent narrator for the greater geopolitical mise-en-scènes of their times, rediscovering a forgotten past. This paper aims to identify the narrativised version of historicity that Anwar considers “authentic” in his novel. The findings propose a reciprocal commitment between narration and history on the basis of lived experiences or memories, phenomenological recurrences, and intersubjective surroundings.